1974
DOI: 10.1116/1.1318662
|View full text |Cite
|
Sign up to set email alerts
|

Processes for multilevel metallization

Abstract: Film deposition and etching techniques for producing multilevel metallized structures on complex devices are reviewed. Emphasis is placed on process procedures for controlled contouring of topographic features induced during pattern etching, techniques for ensuring coverage by deposited films of topography introduced into the substrate, and dielectric deposition procedures that enhance breakdown strength and minimize pinholes. Broadly, the classes of processes discussed are the following: (i) metallization tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Materials that have been used for this purpose include thick films of plasma-deposited nitrides and oxide, spun-on glass (SOG), organic photoresists, polyimides, and flowed phospho rus-doped silicon oxide (P glass) [117,118]. Planarization of topographical features, particularly those of silicon oxide over polysilicon or other materials, is desirable in order to improve opportu nities for high-resolution lithography as well as for more uniform step coverage by interconnect metallizations.…”
Section: E Polymersmentioning
confidence: 99%
“…Materials that have been used for this purpose include thick films of plasma-deposited nitrides and oxide, spun-on glass (SOG), organic photoresists, polyimides, and flowed phospho rus-doped silicon oxide (P glass) [117,118]. Planarization of topographical features, particularly those of silicon oxide over polysilicon or other materials, is desirable in order to improve opportu nities for high-resolution lithography as well as for more uniform step coverage by interconnect metallizations.…”
Section: E Polymersmentioning
confidence: 99%
“…1 The step coverage has been previously reported to depend on deposition parameters, including deposition temperature, total gas flow, and substrate material. [1][2][3][4][5][6][7] Low pressure CVD ͑LPCVD͒ yields better step coverage than PECVD and PECVD provides better step coverage than atmospheric pressure CVD ͑APCVD͒. 4,5 The application of plasma deposition in the microelectronics industry began in 1963.…”
Section: Introductionmentioning
confidence: 99%
“…One fact that is uncontested, however, is that high Se pressure dopes CuInSe2 samples p-type at elevated temperatures. Parkes et al 7 found that a 15-min anneal at 600 °C under an excess of Se pressure (>3 X 104 Pa) was sufficient to type convert an n-type sample to p-type.…”
Section: Resultsmentioning
confidence: 99%